PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE BAMBOO DANCING TERHADAP KEMAMPUAN BERBICARA SISWA KELAS IV SD NEGERI 53 LATTEKKO KECAMATAN AWANGPONE KABUPATEN BONE - Muin, Awaluddin; Jafar, Muh.Idris; Anugrah, Wafdah (MACCA : Science-Edu Journal, 2025)
This research is a quantitative research type of experimental research with a pre-experimental design in the form of a one-group pretest-posttest design which aims to determine whether or not there is a significant effect of the use of the Bamboo Dancing cooperative learning model on the speaking ability of fourth grade students of SD Negeri 53 Lattekko. The variables in this study are the Bamboo Dancing cooperative learning model (independent variable), and speaking ability (dependent variable). The population in this study were all fourth grade students of SD Negeri 53 Lattekko as many as 22 students. This study uses a non-probability sampling technique or saturated samples. The data collection technique for this study is an oral test. The data analysis technique of this study is descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that descriptively the average value of the pretest results is 56.81 while the average posttest result is 77.27. Based on the results of the inferential analysis using the Wilcoxon Signed Ranks Test, it shows that there is a significant difference in students' speaking ability before and after the use of the Bamboo Dancing cooperative learning model. So it can be concluded that there is a significant influence of the use of the Bamboo Dancing cooperative learning model on the speaking ability of fourth grade students of SD Negeri 53 Lattekko, Awangpone District, Bone Regency.